Pemikiran I. Pavlov dan B.F. Skinner dan Implementasinya dengan Layanan BK - Daulay, Maslina; Karneli, Yeni (Jurnal Al-Irsyad: Jurnal Bimbingan Konseling Islam, 2024)
Guidance and counseling (GC) services play an important role in supporting the optimal development of students, with assessment as the foundation. Assessment enables counselors to understand students' conditions and needs in order to design appropriate counseling programs. This research examines the relevance and potential application of the learning theories of I. Pavlov (classical conditioning) and B.F. Skinner (operant conditioning) in improving the effectiveness of counseling services, given the challenges in the practice of assessment in the field, such as limited counselor understanding and limited time and resources. Using the library research method, this study analyzes qualitative data from various literature sources. Results indicate that by providing an understanding of how behavior can be learned and modified, Pavlov's and Skinner's theories are relevant to counseling. Their application allows counselors to design effective interventions such as counterconditioning to overcome anxiety, positive reinforcement to increase motivation, and behavior shaping to develop positive behaviors. Integrating learning theory into the practice of counseling services will result in more effective and holistic services that help students achieve optimal development.